UNA EXPERIENCIA DE EXTENSIÓN RURAL UNIVERSITARIA EN TIEMPOS DEL AISLAMIENTO SOCIAL, PREVENTIVO Y OBLIGATORIO (FAVE Sección Ciencias Veterinarias, 2022)
This paper attempts to reflect the vicissitudes of a university extension project in full social, preventive and compulsory isolation as a result of the Covid 19 pandemic. "The exchange of knowledge in sheep culture", designed to be developed in the dispersed rural areas through workshops and face-to-face training, had to be reoriented towards a completely virtual modality that generated concerns and tensions, capacities and emergencies. It reflects critically on the technological gap, inequality and the rural-urban dichotomy.
Keywords: University extensión, pandemic, virtual modality, ovine.